2000
DOI: 10.1021/la0004909
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Micellization of Zirconyl 2-Ethyl Hexanoate via Small-Angle Neutron and X-ray Scattering

Abstract: We report the first investigation of zirconyl 2-ethyl hexanoate micelles in decane using small-angle neutron and X-ray scattering. Our results show that the micelles have a spherical shell structure consisting of an inner core region with a radius of 6.3 Å that is surrounded by a shell 5.3 Å thick incorporating the surfactant chain segments. From the contrast variation experiment, we calculated there were 33 surfactant molecules/micelle. Finally, our small-angle neutron scattering experiments performed at 80 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Using small-angle neutron scattering (SANS), Kotlarchyk et al reported that AOT micelles are spherical with a hydrodynamic diameter of 3.2 nm [35]. ZrO(Oct) 2 reverse micelles were studied by Keir et al with SANS and small angle X-ray scattering (SAXS) and found to have a diameter of 2.4 nm [36]. The diameter of OLOA 11,000 reverse micelles has been reported by a number of investigators to be about 10 nm [17,32].…”
Section: Resultsmentioning
confidence: 99%
“…Using small-angle neutron scattering (SANS), Kotlarchyk et al reported that AOT micelles are spherical with a hydrodynamic diameter of 3.2 nm [35]. ZrO(Oct) 2 reverse micelles were studied by Keir et al with SANS and small angle X-ray scattering (SAXS) and found to have a diameter of 2.4 nm [36]. The diameter of OLOA 11,000 reverse micelles has been reported by a number of investigators to be about 10 nm [17,32].…”
Section: Resultsmentioning
confidence: 99%
“…All solutions were sealed and stored under dry nitrogen to minimize water adsorption. The volume fraction of surfactant ϕ m was calculated by assuming ideal mixing behavior and using the densities of decane (0.73 g cm −3 ), dodecane (0.75 g cm −3 ), AOT (1.13 g cm −3 ), Zr(Oct) 2 (2.15 g cm −3 ), and PHSA−PMMA (1.04 g cm −3 ).…”
Section: Methodsmentioning
confidence: 99%
“…The PHSA-PMMA copolymer was purified by precipitation from cold methanol, dried at 45 • C overnight and redissolved in dodecane at 140 • C. Micellar solutions were prepared in either dodecane (Acros, 99 %) or decane (Acros, 99 %), which were dried with activated molecular sieves (Acros, size 4A) prior to use. 31 Keir et al 32 Papworth 33…”
Section: Micellar Solutionsmentioning
confidence: 99%
“…The organic ion EH is a branched six-carbon carboxylate, as well as an isomer of n-octanoate, which is a well-known surfactant; 6 however, there are few reports in the literature dealing with surface-active properties of EH salts. Micellization of zirconyl EH in decane was reported by Keir and Watson, 7 and Andor et al 8 stated that zinc EH micellizes in chlorinated hydrocarbons at concentrations higher than 0.1 M. These systems appear to be attractive candidates for precursors, generating micelles which could yield nanoparticles after appropriate coordination. In the literature there are various examples of nanoparticle synthesis using photochemical approaches, as well as compartmentalized media such as reverse micelles (RMs) and the use of both concepts together.…”
Section: ' Introductionmentioning
confidence: 91%